2009
DOI: 10.1021/jf802963h
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Essential Oil Compounds from Different Syrian Populations of Origanum syriacum L. (Lamiaceae)

Abstract: The chemical compositions of the essential oil compounds of 117 individual plants belonging to 11 Syrian populations of Origanum syriacum L. (Lamiaceae) were studied by GC-FID and GC-MS. The composition was dominated by carvacrol and/or thymol with a high degree of polymorphism in the occurrence of these two compounds between the different populations. In three populations carvacrol was dominating, with thymol being present only in minor amounts, whereas in only one population thymol was the main compound, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 30 publications
6
45
0
2
Order By: Relevance
“…EO has been found widely applications in many areas such as medicine and pharmaceutical, cosmetic, agricultural and food industries (Bakkali et al, 2008;Lukas et al, 2009 (Dutra et al, 2009b). A predominance of sesquiterpene was found analyzing the chemical composition of EO from P. emarginatus seeds, being trans-caryophyllene the one in highest concentration.…”
Section: Resultsmentioning
confidence: 99%
“…EO has been found widely applications in many areas such as medicine and pharmaceutical, cosmetic, agricultural and food industries (Bakkali et al, 2008;Lukas et al, 2009 (Dutra et al, 2009b). A predominance of sesquiterpene was found analyzing the chemical composition of EO from P. emarginatus seeds, being trans-caryophyllene the one in highest concentration.…”
Section: Resultsmentioning
confidence: 99%
“…in YES broth, at a concentration of 0.1 mL/mL [18]. Additionally, the carvacrol and thymol were identified as the main components of the oregano E.O, responsible for its antifungal activities [19,20,21]. Similarly, the E.O of the thyme also showed an antifungal effect on the growth of F. verticillioides , A. parasiticus , A. flavus and A. parasiticus due to the presence of the thymol, thyme’s main component [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…While the fatty acids in the OS essential oil generally contains polymorphic compounds, such as thymol and carvacrol, compounds, such as γ-terpinene, P-cymene, and thymoquinene, can also be found depending on the growing area (Lukas et al, 2009) . Some studies have reported that essential fatty acids in OS have antioxidant (Luna et al, 2010;Tavarez et al, 2011), anti-microbial (Mitsch et al, 2004;Gürakan et al, 2008), anti-inflammatory (Yoshino et al, 2006), anti-viral (Pilau et al, 2011), anti-tumoral (El-desoukya et al, 2009Al-kalaldeh et al, 2010), anti-ulcer (Afify et al, 2012), anti-fungal (Manohar et al, 2001), and anti-parasitic (Değerli et al, 2012;Remmal et al, 2013) properties, all of which have positive effects on stock performance (Jang et al, 2007;Tekçe & Gül, 2016).…”
Section: Effects Of Origanum Syriacum Essential Oil On Blood Parametementioning
confidence: 99%